(3GdeWdH GdYGdi aj TQM hSjW GdZRGdis - (3CMeO Hf eMeO Hf Ydj GdCfUGQj, CHh GdYHGS, fLe GdOjf, GdeYQha HGHf GdpqQranYI , J (B710 (3g` s; (3GdZRGdj , MLI GdESdGe CHh MGeO eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj, MLI GdGSdGe GdZRGdj,J (B505 (3g` s
(3BNQgG (B:s
(3BNQ GdaUd GdQGHY ai cHbjI GdGSJfLGA jJdhg ai GdKGfi (B: (3CSHGH GdMOK s
(3GYWi faS Qbe gPG GdcJGH ai GdecJHI hgh (B" 1130 " (3dcJGH fgGjI GdeWdH ddLhjfi Ydi CfgeG cJGH hGMOs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B22 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B266 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B79s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B11 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B2008s
Keywords: (3Gdabg GdTGaYjs